Combined Treatment for Obesity and Depression: A Pilot Study. Issue 7 (22nd June 2018) - Faulconbridge, Lucy F.; Driscoll, Colleen F. B.; Hopkins, Christina M.; Bailer Benforado, Brooke; Bishop‐Gilyard, Chanelle; Carvajal, Raymond; Berkowitz, Robert I.; DeRubeis, Robert; Wadden, Thomas A.
Abstract : Objective: Obesity and depression frequently co‐occur, and each increases risk for cardiovascular disease (CVD). This study tested whether a combined treatment, targeting obesity and depression simultaneously, would yield greater improvements in weight, mood, and CVD risk factors than treatments that targeted each disease individually. Methods: Seventy‐six participants with obesity and major depression were randomly assigned to (1) behavioral weight control (BWC), (2) cognitive behavioral therapy for depression (CBT‐D), or (3) BWC combined with CBT‐D. Participants were provided 18 group treatment sessions over 20 weeks. Mood, weight, and CVD risk were assessed at baseline and weeks 8 and 20, with a follow‐up visit at week 46. Results: At week 20, participants in combined treatment lost significantly ( P < 0.02) more weight (5.2% ± 1.2%) than those assigned to CBT‐D (0.8% ± 1.3%) and comparable amounts as those in BWC (3.5% ± 1.3%). Depression scores decreased significantly from baseline levels in each group, with no significant differences between groups. All three groups showed significant improvements in 10‐year CVD risk, with no significant differences between groups. Groups did not differ significantly on any of these measures at week 46. Conclusions: BWC yielded short‐term improvements in weight, mood, and CVD risk, comparable to a combined treatment that incorporated CBT‐D. Results require replication with a larger sample size.